BIOFILM PRODUCTION AMONG UROPATHOGENS AND THEIR ANTIBIOGRAM - N.V.ABDAGIRE,; V.V CHINCHOLKAR,; D.M KULKARNI,; S.L NILEKAR,; S.V. BIRAJDAR, (International Journal of Pharma and Bio Sciences, 2014)
Urinary tract infection (UTI) is the most commonly acquired bacterial infection. Antibiotic resistance of uropathogens has been known to increase worldwide and biofilm production being the prime cause. The objective of this study was to detect the production of biofilm by uropathogens isolated from UTIs and their antimicrobial susceptibility pattern. A total 570 urine samples from clinically suspected UTI patients were processed by standard microbiological procedures. The isolated uropathogens were tested to biofilm production by Congo Red agar method and tube adherence method. Antimicrobial susceptibility testing of uropathogens was done by Kirby – Bauer disc diffusion method. Out of 272 cultures positive cases, Eshcherichia coli was the commonest uropathogen isolated followed by Staphylococcus aureus and Klebsiella pneumoniae. The antimicrobial susceptibility pattern of biofilm producers showed high resistance to commonly used antibiotics. The present study showed significant correlation between biofilm production and antibiotic resistance, so it is necessary to screen all isolates for biofilm production.